Analisis Penerapan Biaya Lingkungan Studi Kasus Pada Rumah Sakit Islam Banjarmasin - Noor, Fatmawati Bakri; Adriani, Ade; Norlena; Riyadi, Padlah (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This study aims to uncover waste management activities and environmental costs of environmental cost reporting at the Islamic Hospital of Banjarmasin. This researcher uses a qualitative paradigm with a case study design. The research scope is the Unit of Environmental Health Sanitation with the accounting process of environmental management, hospital waste management's data focus, and expenditures for waste costs. Primary data were collected through in-depth interviews and observations; secondary data, through documentation. The results revealed that environmental management accounting systems in 2019 and 2020 found hidden environmental costs from waste management cost reports in the Financial Statements. For example, the environmental cost report applied to the SKL Unit revealed Rp 677.646.500 and Rp 459.521.600 not presented as an environmental cost in 2019 and 2020. The implementation of environmental cost accounting through environmental cost reporting at the Islamic Hospital of Banjarmasin revealed that special reports in environmental management accounting could be used as information by the management of the Islamic Hospital of Banjarmasin in planning and controlling environmental responsibility activities. The study results also revealed that the environmental cost report facilitated the direction of the Islamic Hospital of Banjarmasin in making decisions related to environmental costs and provided information for stakeholders that hospitals have been responsible for maintaining environmental health.